Determinants of China’s economic engagement with oil and minerals exporting African countries / Gold Kafilah Lola - Gold Kafilah , Lola (2019)
Many times, the engagement between China and Africa is stereotyped as an energy quest to sustain China’s economic growth, leading to anti-Chinese narratives in Africa. Against this background, the observed presence of China in the top 18 oil/minerals exporting countries in Africa warrants special attention, as the strategic engagement has expanded significantly to emerge as a powerful, yet questionable, South-South alliance. In this study, the determinants of China’s economic activities in Africa are derived through the three dominant economic linkages of trade, foreign direct investment (FDI) and aid/financial flows; using data over the period of 1992-2015. To achieve the objectives of this study, the UN-Comtrade trade data, based on the Harmonized System (HS) nomenclature is used to classify into agriculture, oil/minerals and manufacturing. The gravity model (GM), fixed effects (FE), Generalised Least Squares (GLS), Poisson Pseudo – Maximum Likelihood (PPML) and the Least Squares Dummy Variable (LSDV) estimators were deployed to analyse trade. The results indicate that China’s oil/minerals imports are higher than in manufacturing and agriculture. Also, GDP, population and trade openness are determinants of trade. However, the distance between China and Africa reduced trade. Also, institutional quality (political instability and corruption), spur trade. In objective two, GLS and Instrumental Variable 2-Stage Least Squares (2SLS) were deployed to identify the imports sector(s) and other determinants of China’s FDI stocks and flows. The results indicate that FDI stocks are less volatile than flows, but FDI flows have more explanatory power than FDI stocks. The results of FDI stocks indicate that oil/minerals and agricultural imports facilitate more stocks. While the institutional variable proxy of political instability has an overall negative and significant impact on FDI stocks. The results indicate a positive and strongest statistical significance on oil/minerals imports. Also, the institutional variable (political instability) shows a negative, but significant relationship with imports. The third objective examines the determinants of China’s foreign aid to Africa, and whether it is determined by altruism or by trade-benefits. These twofold objectives were carried out using China’s bilateral loan data obtained from the China Africa Research Initiative (CARI). In the trade disaggregate data used, imports were used to examine the altruism motive for giving aid while disaggregated export data were used to analyse aid-for-trade-benefits. Using the FE, GLS and Pesaran dynamic fixed effects techniques, the results show that oil/minerals are not the determinants of aid in the two specified equations, however, aid is tied to China’s manufacturing exports. The findings on the institutional variables (political instability and corruption) show that a decrease in political instability and corruption reduce China’s aid. Related results apply to external debt and infant mortality rate as the analyses show that they are important determinants in China’s bilateral aid considerations to Africa. The findings of this study should serve as recommendations for policymakers to improve trade policies that will enhance the sustainability of Africa’s engagement with China.